Resistance against religious intolerance in Indonesia contemporary indie songs - Prawadika Aji, Angga; Mauradiva, Adinda; Kurniawan, Ferhandito (Jurnal Studi Komunikasi, 2021)
This study sought to examine any form of criticism and resistance against the growing religious intolerance in Indonesian contemporary indie songs. The study of indie music is often marginalised in media and communication studies, even though the music itself is an effective form of media to convey socio-political messages. Indie music shows an increasingly crucial role within the map of cultural products in Indonesia mainly because it is considered an important means of conveying messages and alternative media for new Indonesian youth. Indie musicians cover sensitive issues within their lyric, including religious intolerance perpetrated by conservative Muslim groups in Indonesia. Through the discourse analysis method by Teun Van Dijk, this study found three forms of resistance discourse found in Indonesian indie music: a critique towards middle-class Muslims hypocrisy, rejection against the imposition of the sharia law, and the lament over the loss of humanity in religious practice. The research findings show that indie songs serve as a medium of resistance to a more secular, youthful audience against many issues seldom covered in mainstream media.